Uncovering Historical Legacies to Contextualize Health Inequities in Puerto Rican Men: An Expansion of the Minority Stress Model - Valdez, Luis A.; Mullany, Anna; Barbieri, Marielena; Gubrium, Aline (Frontiers in Sociology, 2022)
Background: Low/no-income Latino men are disproportionately burdened by chronic disease morbidity and mortality, which is often compounded by persistent exposure to stress. Chronic stress is a key mediating factor in pathways linking macro-level socio-structural forces to micro-level behavioral factors with negative health outcomes. Being that Latinxs continue to be one of the fastest growing populations in the U.S., it is imperative to better understand the roots of stress pathways and explore multi-level interventions. Methods: This study presents qualitative findings from in-depth interviews with Puerto Rican men (95%) living in Springfield, Massachusetts. We utilized the Minority Stress Model (MSM) first posited by Ilan Meyers, as a framework to understand stress and stress processes amongst Puerto Rican men. We mapped our data onto Meyers’ MSM, which allowed us to find diverging themes and identify areas for expansion. Results: As expected, participants reported stress rooted in experiences of racism and prejudice, expectations of rejection, English-language acquisition, family relationships, insecure housing, precarious employment, and lack of resources. Nevertheless, the MSM did not account for the historical contexts that, as our findings indicate, are used to filter and understand their experiences with everyday stressors. Participants described and linked histories of colonial violence and movement and migration to their stress and community well-being. Discussion: Findings suggest the need to expand the current MSM and our conceptualization of the stress process to include historical understandings when contextualizing present-day stress and future interventions. We propose an expanded heuristic model that delineates the impact of distinctive historical trajectories that aid in interpreting racial health disparities amongst minoritized populations. Future multi-level interventions should give weight to highlighting history and how this impacts the present, in this case including the culpability of U.S. policy regarding Puerto Rico and the adverse health effects for Puerto Rican men on the mainland.